High-fluorine lithium aluminate salt and preparation method and application thereof, electrolyte and application thereof, and lithium battery
By adding high fluoro-aluminate to the lithium battery electrolyte, the problems of increasing impedance and decreasing capacity caused by anion migration at high operating current density of lithium batteries are solved, and the formation of solid electrolyte interface film is participated in the formation of a solid electrolyte interface film during the cycle, achieving high magnification, long cycle and stable performance of lithium batteries.
Patent Information
- Application Number
- CN202411908051.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The concentration polarization caused by anion migration at high operating current density of existing lithium batteries leads to an increase in impedance and a sharp drop in capacity. At the same time, the solid electrolyte interface film produced by conventional lithium salt electrolytes is harmful to the performance of lithium batteries.
The lithium high-fluoroluminate is used as an additive to the electrolyte, and the electrolyte is formed by mixing it with the commercial alkali carbonate electrolyte. It uses its intramolecular lithium oxygen action and pseudo-crown ether structure to enhance the number of lithium ions and participate in the formation of the solid electrolyte interface film during the circulation process.
The high-rate fast charging and discharge and long cycle capabilities of lithium batteries are improved, and the problems of increasing impedance and reducing capacity of batteries under high loads are reduced. By forming a stable and efficient solid electrolyte interface, the electrode is protected and the growth of lithium dendrites is inhibited.
Smart Images

Figure CN119725748A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, and in particular to high-fluorine aluminate lithium salts and preparation methods and applications thereof, electrolytes and applications thereof, and lithium batteries. Background Art
[0002] Lithium-ion batteries are widely used in portable electronics, electric vehicles, and stationary grid energy storage devices. Salts in lithium-ion batteries play a crucial role in battery performance. They are the main source of free conductive lithium ions and also dominate the formation of solid electrolyte interface (SEI) at the electrode. LiPF6 is the most commonly used salt in rechargeable lithium metal batteries (LMBs) due to its optimal combination of ionic conductivity, electrochemical window, and electrode interface properties. As commercial lithium salts with symmetrical molecular geometry (LiPF6, LiTFSI, etc.), they have high ionic conductivity but low lithium ion transference number (tLi + ). Generally, it is widely believed that Li + The migration of anions determines the rate capability of lithium batteries. At high operating current density, the migration of anions produces concentration polarization, resulting in increased impedance and a sharp drop in capacity, which is especially true for carbonate-based electrolytes. In addition, carbonate electrolytes using these conventional lithium salts will produce organic-rich solid electrolyte interface films (SEI, CEI), which are detrimental to the performance of lithium batteries. Therefore, the development of a new type of lithium salt additive with high rate, long cycle and the ability to construct a stable and efficient solid electrolyte interface is an important research and application direction. Summary of the invention
[0003] The purpose of the present invention is to provide a high-fluorine aluminate lithium salt and a preparation method and application thereof, an electrolyte and its application, and a lithium battery. The high-fluorine aluminate lithium salt as an additive to the electrolyte can improve the high-rate rapid charge and discharge and long-cycle capabilities of the lithium battery.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a high-fluorine aluminate lithium salt, the preparation raw materials of which include diethylene glycol monomethyl ether compounds, high-fluorine tert-butyl alcohol compounds and lithium aluminum hydride;
[0006] The molar ratio of the diethylene glycol monomethyl ether compound, the high-fluorinated tert-butyl alcohol compound and lithium aluminum hydride is (0.5-2): (1-6): (0.5-2).
[0007] Preferably, the diethylene glycol monomethyl ether compound includes one or more of ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, heptaethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, triethylene glycol monomethyl ether and eicosyl (ethylene glycol) monomethyl ether.
[0008] Preferably, the high-fluorinated tert-butyl alcohol compound includes one or more of perfluoropropanol, hexafluoropropanol, perfluoro-n-butyl alcohol, perfluoro-tert-butyl alcohol, heptafluoro-n-butyl alcohol, heptafluoro-tert-butyl alcohol and perfluoroheptanol.
[0009] The present invention also provides a method for preparing the high-fluorinated lithium aluminate salt described in the above technical solution, comprising the following steps:
[0010] In a protective atmosphere, diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride are subjected to a dehydrogenation reduction reaction to obtain the high-fluorinated lithium aluminate salt.
[0011] Preferably, the dehydrogenation reduction reaction comprises a first reaction and a second reaction performed sequentially;
[0012] The temperature of the first reaction is -48 to 120°C and the time is 3 to 8 hours;
[0013] The temperature of the second reaction is room temperature, and the time is 12 to 24 hours.
[0014] The present invention also provides the use of the high-fluoroaluminate lithium salt described in the above technical solution or the high-fluoroaluminate lithium salt prepared by the preparation method described in the above technical solution as an additive in an electrolyte.
[0015] The present invention also provides an electrolyte, comprising a commercial alkaline carbonate electrolyte and a high-fluorinated lithium aluminate salt;
[0016] The high-fluoroaluminate lithium salt is the high-fluoroaluminate lithium salt described in the above technical solution or the high-fluoroaluminate lithium salt prepared by the preparation method described in the above technical solution.
[0017] Preferably, the usage ratio of the high-fluorinated lithium aluminate salt to the commercial alkaline carbonate electrolyte is (0.05-1) mol:1L.
[0018] The present invention also provides the use of the electrolyte described in the above technical solution in a lithium battery.
[0019] The present invention also provides a lithium battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the electrolyte described in the above technical solution.
[0020] The invention provides a high-fluorine aluminate lithium salt. The preparation raw materials include diethylene glycol monomethyl ether compounds, high-fluorine tert-butyl alcohol compounds and lithium aluminum hydride. The molar ratio of the diethylene glycol monomethyl ether compounds, the high-fluorine tert-butyl alcohol compounds and the lithium aluminum hydride is (0.5-2): (1-6): (0.5-2). The high-fluorinated lithium aluminate salt of the present invention is applied as an electrolyte additive to a carbonate electrolyte. Due to the lithium-oxygen interaction within the molecule, the molecule presents a pseudo-crown ether conformation, and the anion part drives the lithium ions to move together, thereby weakening the solvation of the lithium ions and increasing the number of lithium ion migration in the electrolyte. This can effectively solve the problem that the mobile anions of the carbonate-based electrolyte produce concentration polarization under high working current density, resulting in increased impedance and a sharp decrease in capacity. In addition, the high-fluorinated lithium aluminate salt participates in the formation of a solid electrolyte interface film during the battery cycle, and the decomposition product is rich in inorganic substances such as fluoride and aluminide, which is beneficial to protecting the electrode, inhibiting the growth of lithium dendrites, and obtaining excellent cycle performance. The high-fluorinated lithium aluminate salt can be applied as an additive to the electrolyte in a secondary lithium ion battery.
[0021] The present invention also provides a method for preparing the high-fluorinated lithium aluminate salt described in the above technical solution, comprising the following steps: in a protective atmosphere, dehydrogenating and reducing diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride to obtain the high-fluorinated lithium aluminate salt. The preparation method is simple in process, short in preparation cycle, simple in preparation equipment and easy to operate, and convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the high fluoroaluminate lithium salt described in Example 1;
[0023] Figure 2 The polarization voltage and capacity diagram of the electrolyte described in Example 8 cycled at 5C;
[0024] Figure 3 1 is a cycle diagram of the electrolyte described in Example 8 and the commercial alkaline carbonate electrolyte described in Example 8 at a high rate (5C);
[0025] Figure 4 The graphs are the charge and discharge cycle performances of the electrolyte described in Example 8 and the commercial alkaline carbonate electrolyte described in Example 8 at different currents. DETAILED DESCRIPTION
[0026] The invention provides a high-fluorine aluminate lithium salt, the preparation raw materials of which include diethylene glycol monomethyl ether compounds, high-fluorine tert-butyl alcohol compounds and lithium aluminum hydride;
[0027] The molar ratio of the diethylene glycol monomethyl ether compound, the high-fluorinated tert-butyl alcohol compound and lithium aluminum hydride is (0.5-2): (1-6): (0.5-2).
[0028] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0029] In the present invention, the diethylene glycol monomethyl ether compound preferably includes one or more of ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, heptapolyethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, triethylene glycol monomethyl ether and icosyl (ethylene glycol) monomethyl ether, and more preferably includes ethylene glycol monomethyl ether or diethylene glycol monomethyl ether; when the diethylene glycol monomethyl ether compound is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0030] In the present invention, the high-fluorinated tert-butanol compound preferably includes one or more of perfluoropropanol, hexafluoropropanol, perfluoro-n-butanol, perfluoro-tert-butanol, heptafluoro-n-butanol, heptafluoro-tert-butanol and perfluoroheptanol, and more preferably includes perfluoro-tert-butanol, hexafluoropropanol, perfluoro-n-butanol, heptafluoro-tert-butanol, perfluoroheptanol or hexafluoropropanol; when the high-fluorinated tert-butanol compound is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0031] In the present invention, the molar ratio of the diethylene glycol monomethyl ether compound, the high-fluorinated tert-butyl alcohol compound and lithium aluminum hydride is (0.5-2):(1-6):(0.5-2), preferably 1:3:1.
[0032] In the present invention, the raw materials for preparing the lithium perfluoroaluminate salt preferably also include an organic solvent, and the organic solvent preferably includes one or more of tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) and acetonitrile (MeCN), more preferably THF; when the organic solvent is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.
[0033] In the present invention, the molar amount of the diethylene glycol monomethyl ether compound and the volume ratio of the organic solvent are preferably (0.005-0.05) mol: (25-30) mL. In an embodiment of the present invention, the molar amount of the diethylene glycol monomethyl ether compound and the volume ratio of the organic solvent can be 0.005 mol: 25 mL.
[0034] In the present invention, the purity of the high-fluoroaluminate lithium salt is preferably ≥98%.
[0035] The present invention also provides a method for preparing the high-fluorinated lithium aluminate salt described in the above technical solution, comprising the following steps:
[0036] In a protective atmosphere, diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride are subjected to a dehydrogenation reduction reaction to obtain the high-fluorinated lithium aluminate salt.
[0037] In the present invention, the protective atmosphere is preferably a nitrogen atmosphere or an argon atmosphere.
[0038] In the present invention, the process of dehydrogenation reduction reaction of diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride is preferably to mix diethylene glycol monomethyl ether compounds and high-fluorinated tert-butyl alcohol compounds, organic solvents and lithium aluminum hydride to carry out dehydrogenation reduction reaction. In the present invention, the mixing preferably includes mixing diethylene glycol monomethyl ether compounds and high-fluorinated tert-butyl alcohol compounds in a protective atmosphere, adding an organic solvent for first mixing, and then adding lithium aluminum hydride. In the present invention, the first mixing is preferably carried out under stirring, and the stirring temperature is preferably -48 to -78°C, more preferably -48°C or -78°C; the time is preferably 20 to 30 min, more preferably 25 to 30 min, and most preferably 30 min; the stirring speed is preferably 900r / min. In the present invention, the lithium aluminum hydride is preferably added dropwise in the form of a solution, and the concentration of the lithium aluminum hydride solution is preferably 0.8 to 2.5 mol / L, more preferably 1.5 to 2.5 mol / L, and most preferably 2.5 mol / L. The present invention does not have any special restrictions on the process of adding dropwise, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the stirring temperature can be -78°C, the time can be 30 min; the rotation speed can be 900 r / min; the concentration of the lithium aluminum hydride solution can be 1 mol / L.
[0039] In the present invention, the dehydrogenation reduction reaction preferably includes a first reaction and a second reaction performed sequentially, the temperature of the first reaction is preferably -48 to 120°C; the time is preferably 3 to 8 hours, more preferably 3 to 6 hours, and most preferably 3 hours; the temperature of the second reaction is preferably room temperature; the time is preferably 12 to 24 hours, more preferably 18 to 24 hours, and most preferably 24 hours. In an embodiment of the present invention, the temperature of the first reaction can be -78°C and the time can be 3 hours; the temperature of the second reaction can be room temperature and the time can be 24 hours.
[0040] After the dehydrogenation reduction reaction is completed, the present invention also preferably includes extraction and drying performed in sequence; the extraction is preferably performed using n-hexane. In the present invention, the drying is preferably vacuum drying, and the present invention has no special restrictions on the process of vacuum drying, and the process well known to those skilled in the art can be used.
[0041] The present invention also provides the use of the high-fluoroaluminate lithium salt described in the above technical solution or the high-fluoroaluminate lithium salt prepared by the preparation method described in the above technical solution as an additive in an electrolyte.
[0042] The present invention also provides an electrolyte, comprising a commercial alkaline carbonate electrolyte and a high-fluorinated lithium aluminate salt;
[0043] The high-fluoroaluminate lithium salt is the high-fluoroaluminate lithium salt described in the above technical solution or the high-fluoroaluminate lithium salt prepared by the preparation method described in the above technical solution.
[0044] In the present invention, the usage ratio of the high fluoroaluminate lithium salt to the commercial alkaline carbonate electrolyte is preferably (0.05-1) mol: 1 L, more preferably (0.2-0.8) mol: 1 L, and most preferably (0.4-0.6) mol: 1 L. In an embodiment of the present invention, the usage ratio of the high fluoroaluminate lithium salt to the commercial alkaline carbonate electrolyte can be 0.05 mol: 1 L, 0.1 mol: 1 L, 0.2 mol: 1 L, 0.5 mol: 1 L, 0.8 mol: 1 L, 1 mol: 1 L.
[0045] In the present invention, the commercial alkaline carbonate electrolyte preferably includes a lithium salt and a solvent; in the present invention, the concentration of the lithium salt in the commercial alkaline carbonate electrolyte is preferably 0.5 to 3 mol / L, more preferably 1 to 2 mol / L. In an embodiment of the present invention, the concentration of the lithium salt in the commercial alkaline carbonate electrolyte may be 1 mol / L. In the present invention, the solvent preferably includes dimethyl carbonate and ethylene carbonate; the mass ratio of dimethyl carbonate to ethylene carbonate is preferably (1 to 2): (1 to 3). In an embodiment of the present invention, the mass ratio of dimethyl carbonate to ethylene carbonate may be 1:1; the dimethyl carbonate is also preferably replaced by one or more of fluorocarbonate, diethyl carbonate, propylene carbonate, ethyl methyl carbonate, methyl pyruvate and vinylene carbonate.
[0046] In the present invention, the lithium salt preferably includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium difluorooxalate borate, lithium bis(trifluoromethylsulfonyl imide), lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl imide), lithium tetrachlorogallate and lithium perchlorate. When the lithium salt is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, the purity of the lithium salt is preferably ≥99%.
[0047] In the present invention, the method for preparing the electrolyte preferably comprises the following steps:
[0048] The perfluoroaluminate lithium salt is mixed with a commercial alkaline carbonate electrolyte to obtain the electrolyte.
[0049] In the present invention, the commercial alkaline carbonate electrolyte is preferably obtained by dissolving a lithium salt in a solvent.
[0050] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention does not have any special limitation on the stirring process, and the stirring process may be carried out using a process well known to those skilled in the art.
[0051] The present invention also provides the use of the electrolyte described in the above technical solution in a lithium battery.
[0052] The present invention also provides a lithium battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is metallic lithium, and is characterized in that the electrolyte is the electrolyte described in the above technical solution.
[0053] In the present invention, the positive electrode includes a current collector and a positive electrode material coated on the surface of the current collector; the positive electrode material preferably includes one or more of graphite, NCM622, NCM811, LFP and LNMO. When the positive electrode material is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, the material of the current collector is preferably stainless steel. In the present invention, the coating amount of the positive electrode material on the surface of the current collector is preferably 0.8 to 1.5 g / cm 2 , more preferably 1.2 to 1.5 g / cm 2 , most preferably 1.5 g / cm 2 .
[0054] In the present invention, the negative electrode is preferably metallic lithium.
[0055] The following is a detailed description of the high-fluorinated lithium aluminate salt and its preparation method and application, the electrolyte and its application, and the lithium battery provided by the present invention in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0056] Example 1
[0057] 10 mmol of diethylene glycol monomethyl ether and 30 mmol of perfluoro tert-butyl alcohol were added to a Schlenk tube in a nitrogen atmosphere, 50 mL of tetrahydrofuran (THF) was added, and after stirring at -78 ° C for 30 min, 10 mL of lithium aluminum hydride (10 mmol) with a concentration of 1 mol / L was dropped, and after stirring at 900 r / min at -78 ° C for 3 h, the mixture was transferred to room temperature for reaction for 24 h, and the product was extracted with n-hexane, and vacuum dried to constant weight to obtain the perfluoroaluminate lithium salt (white crystals);
[0058] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the high fluoroaluminate lithium salt, Figure 1 It can be seen that the chemical shift of the methyl peak e on the product molecule is 3.4, and the integral is 3. The chemical shifts of the methylene a and d are 3.57 and 3.72 respectively, and the integral values are 2. The methylene b and c are coupled, with a chemical shift of 3.64 and an integral value of 4. The H NMR spectrum of the product molecule is consistent with the molecular structure, proving that the molecule was successfully synthesized.
[0059] Example 2
[0060] 10 mmol of diethylene glycol monomethyl ether and 30 mmol of heptafluorobutanol were added to a Schlenk tube in a nitrogen atmosphere, and 50 mL of tetrahydrofuran (THF) was added. After stirring at -78 ° C for 30 min, 10 mL of lithium aluminum hydride (10 mmol) with a concentration of 1 mol / L was dropped, and after stirring at 900 r / min at -78 ° C for 3 h, the mixture was transferred to room temperature for reaction for 24 h, and the product was extracted with n-hexane and vacuum dried to constant weight to obtain the perfluoroaluminate lithium salt (white crystals).
[0061] Example 3
[0062] 10mmol of diethylene glycol monomethyl ether and 30mmol of perfluoro-1-butanol were added to a Schlenk tube in a nitrogen atmosphere, 50mL of tetrahydrofuran (THF) was added, and after stirring at -78°C for 30min, 10mL of 1mol / L lithium aluminum hydride (10mmol) was dropped, and after stirring at 900r / min at -78°C for 3h, the mixture was transferred to room temperature for reaction for 24h, the product was extracted with n-hexane, and vacuum dried to constant weight to obtain the perfluoroaluminate lithium salt (white crystals).
[0063] Example 4
[0064] 10 mmol of diethylene glycol monomethyl ether and 30 mmol of heptafluorobutanol were added to a Schlenk tube in a nitrogen atmosphere, and 50 mL of tetrahydrofuran (THF) was added. After stirring at -78 ° C for 30 min, 10 mL of lithium aluminum hydride (10 mmol) with a concentration of 1 mol / L was dropped, and after stirring at 900 r / min at -78 ° C for 3 h, the mixture was transferred to room temperature for reaction for 24 h, and the product was extracted with n-hexane and vacuum dried to constant weight to obtain the perfluoroaluminate lithium salt (white crystals).
[0065] Example 5
[0066] 10 mmol of diethylene glycol monomethyl ether and 30 mmol of perfluoroheptane were added to a Schlenk tube in a nitrogen atmosphere, 50 mL of tetrahydrofuran (THF) was added, and after stirring at -78 ° C for 30 min, 10 mL of lithium aluminum hydride (10 mmol) with a concentration of 1 mol / L was dropped, and after stirring at 900 r / min at -78 ° C for 3 h, the mixture was transferred to room temperature for reaction for 24 h, the product was extracted with n-hexane, and vacuum dried to constant weight to obtain the perfluoroaluminate lithium salt (white crystals).
[0067] Example 6
[0068] 10 mmol of ethylene glycol monomethyl ether and 30 mmol of hexafluoropropanol were added to a Schlenk tube in a nitrogen atmosphere, and 50 mL of tetrahydrofuran (THF) was added. After stirring at -78 ° C for 30 min, 10 mL of lithium aluminum hydride (10 mmol) with a concentration of 1 mol / L was dropped, and after stirring at 900 r / min at -78 ° C for 3 h, the mixture was transferred to room temperature for reaction for 24 h, and the product was extracted with n-hexane and vacuum dried to constant weight to obtain the lithium perfluoroaluminate salt (white crystals).
[0069] Example 7
[0070] 1 mol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0071] 0.05 mmol of the high-fluoroaluminate lithium salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the high-fluoroaluminate lithium salt was 0.05 mol / L);
[0072] The electrolyte was applied to a battery with NCM622 as the positive electrode and lithium metal as the negative electrode. The battery cycle performance was tested at a current density of 2C, and the first cycle capacity was measured to be 165mA·h·h -1 , after 180 cycles, it provided 81.5% of the capacity.
[0073] Example 8
[0074] 1 mmol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0075] 0.1 mmol of the high-fluoroaluminate lithium salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the high-fluoroaluminate lithium salt was 0.1 mol / L);
[0076] The electrolyte and the commercial alkaline carbonate electrolyte were applied to a battery with NCM622 as the positive electrode and lithium metal as the negative electrode, respectively. The cycle performance of the battery was tested at a current density of 2C, and the first cycle capacity was measured to be 175 mA·h·h -1 , the capacity retention rate dropped to less than 80% of the initial capacity after 240 cycles;
[0077] Figure 2 is the polarization voltage and capacity diagram of the battery composed of the electrolyte cycled at 5C, Figure 2 It can be seen that the battery provides 82% capacity when it is cycled 140 times at a charge and discharge rate of 5C, effectively overcoming the increase in battery overpotential;
[0078] Figure 3 is a cycle diagram of a battery composed of the electrolyte and the commercial alkaline carbonate electrolyte at a high rate (5C), Figure 3 It can be seen that after 150 cycles at 5C, the capacity retention rate of the battery composed of the commercial alkaline carbonate electrolyte is 48.2%, which is due to the continuous capacity decay and increased overpotential during the cycle process. In sharp contrast, under the same conditions, the electrolyte can extend the cycle life and improve the capacity retention rate. The battery operating at 5C maintained 81.5% of its capacity after 220 cycles;
[0079] Figure 4 The charge and discharge cycle performance diagram of the battery composed of the electrolyte and the commercial alkaline carbonate electrolyte at different currents is shown in FIG. Figure 4 It can be seen that the battery composed of the electrolyte exhibits excellent rate capability, with specific capacities of 168 and 152 mA·h·h at 0.2C and 2C, respectively. -1 When the cycle rate increases to 5C and 10C, the specific capacity remains at 141 mA·h·h -1 and 117mA·h·h -1 In comparison, the commercial alkaline carbonate electrolyte battery has a specific capacity of ∼167, 115, and 60 mA·h·h at 0.2, 2, and 5 C, respectively. -1 At 10C, the capacity is limited to ~18 mA h h due to low Coulombic efficiency and increased overpotential. -1 , capacity loss occurs rapidly.
[0080] Example 9
[0081] 1 mol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0082] 0.2 mmol of the lithium perfluoroaluminate salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the lithium perfluoroaluminate salt was 0.2 mol / L);
[0083] The battery cycle performance was tested at a current density of 2C, and the first cycle capacity was measured to be 160mA·h·h -1 , the capacity retention rate dropped to less than 80% of the initial capacity after 175 cycles.
[0084] Example 10
[0085] 1 mol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0086] 0.5 mmol of the lithium perfluoroaluminate salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the lithium perfluoroaluminate salt was 0.5 mol / L);
[0087] The battery cycle performance was tested at a current density of 2C, and the first cycle capacity was measured to be 163mA·h·h -1 , the capacity retention rate dropped to less than 80% of the initial capacity after 175 cycles.
[0088] Embodiment 11
[0089] 1 mol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0090] 0.8 mol of the high-fluoroaluminate lithium salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the high-fluoroaluminate lithium salt was 0.8 mol / L);
[0091] The battery cycle performance was tested at a current density of 2C, and the first cycle capacity was measured to be 166mA·h·h -1 , the capacity retention rate dropped to less than 80% of the initial capacity after 190 cycles.
[0092] Example 12
[0093] 1 mol of lithium salt (lithium hexafluorophosphate) was dissolved in dimethyl carbonate and ethylene carbonate in a mass ratio of 1:1 to obtain a commercial alkaline carbonate electrolyte (the concentration of the lithium salt was 1 mol / L);
[0094] 1 mmol of the high-fluoroaluminate lithium salt described in Example 1 and 1 mL of the commercial alkaline carbonate electrolyte were mixed under stirring to obtain an electrolyte (the concentration of the high-fluoroaluminate lithium salt was 1 mol / L);
[0095] The battery cycle performance was tested at a current density of 2C, and the first cycle capacity was measured to be 157mA·h·h -1 , the capacity retention rate dropped to less than 80% of the initial capacity after 130 cycles.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high fluorine aluminate lithium salt, characterized in that: The preparation raw materials include diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride; The molar ratio of the diethylene glycol monomethyl ether compound, the high-fluorinated tert-butyl alcohol compound and lithium aluminum hydride is (0.5-2): (1-6): (0.5-2).
2. The high fluoroaluminate lithium salt according to claim 1, characterized in that The diethylene glycol monomethyl ether compound includes one or more of ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, heptaethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, triethylene glycol monomethyl ether and icosyl (ethylene glycol) monomethyl ether.
3. The high fluoroaluminate lithium salt according to claim 1, characterized in that The high-fluorinated tert-butyl alcohol compound includes one or more of perfluoropropanol, hexafluoropropanol, perfluoro-n-butyl alcohol, perfluoro-tert-butyl alcohol, heptafluoro-n-butyl alcohol, heptafluoro-tert-butyl alcohol and perfluoroheptanol.
4. The method for preparing the high-fluorinated lithium aluminate according to any one of claims 1 to 3, characterized in that: The following steps are involved: In a protective atmosphere, diethylene glycol monomethyl ether compounds, high-fluorinated tert-butyl alcohol compounds and lithium aluminum hydride are subjected to a dehydrogenation reduction reaction to obtain the high-fluorinated lithium aluminate salt.
5. The preparation method according to claim 4, characterized in that: The dehydrogenation reduction reaction includes a first reaction and a second reaction performed sequentially; The temperature of the first reaction is -48 to 120°C and the time is 3 to 8 hours; The temperature of the second reaction is room temperature, and the time is 12 to 24 hours.
6. Use of the high-fluoroaluminate lithium salt according to any one of claims 1 to 3 or the high-fluoroaluminate lithium salt prepared by the preparation method according to claim 4 or 5 as an additive in an electrolyte.
7. An electrolyte, characterized in that: Including commercial alkaline carbonate electrolytes and lithium perfluoroaluminate salts; The high-fluoroaluminate lithium salt is the high-fluoroaluminate lithium salt described in any one of claims 1 to 3 or the high-fluoroaluminate lithium salt prepared by the preparation method described in claim 4 or 5.
8. The electrolyte according to claim 7, characterized in that The usage ratio of the high-fluorinated lithium aluminate salt to the commercial alkaline carbonate electrolyte is (0.05-1) mol:1L.
9. Use of the electrolyte according to claim 7 or 8 in a lithium battery.
10. A lithium battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the electrolyte according to claim 7 or 8.